Determination of 21 Triazole Fungicides in Fruits and Vegetables by Lipophilicity-matched Chromatographic Separation-Ultra Performance Liquid Chromatography-tandem Mass Spectrometry - Hu MENG; Yuanjin LI; Danni ZHAO; Yating ZHANG; Dan ZHANG; Qi YANG; Xinyi FENG (Shipin gongye ke-ji, 2024)
In order to improve the chromatographic separation efficiency of pesticide residues and reduce matrix effects, a lipophilicity-matched chromatographic separation strategy was proposed in this study. The triazole fungicides in fruits and vegetables were selected as a case study to establish the analytical method of 21 triazole fungicides with ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The samples were extracted by acetonitrile, followed by salting out and cleaned-up with dispersive solid phase extraction, then separated on chromatographic column with similar lipophilicity to triazole fungicides. The effects of alkyl bonded phase with different lipophilicity on the matrix effects, recoveries and chromatographic separation of triazole fungicides and matrix components were explored. The results showed that this strategy could improve the chromatographic separation of triazole fungicides and matrix components. And 21 triazole fungicides had matrix effects within −8.3%~4.7% and good linear relationship within 5~250 μg/L, the determination coefficient R2≥0.999. The average recoveries ranged from 91.4% to 108.1%, while the limits of quantitation were in the range of 0.5~3.5 μg/kg. This method could effectively reduce matrix effects and provide satisfactory recoveries using solvent calibration for quantification, which could significantly improve the detection efficiency. The proposed method was simple, accurate and sensitive, and suitable for determination of triazole fungicides in fruits and vegetables. This strategy could provide a method reference for column selection and matrix effect reduction in liquid chromatography-tandem mass spectrometry analysis.